Transforming rural economies through tertiary education: Evidence from India - Amparo Castelló-Climent; Abhiroop Mukhopadhyay; Ravinder (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper analyses the role of tertiary education on rural development. Using census data on villages in India for 2011, we find that skilled workers have had an important impact on rural prosperity. A 1 percentage point rise in the share of the village population with tertiary education raises per capita consumption by around 7.2 per cent. Our results are robust to alternative measures of income and are not confounded by better institutions. Among the mechanisms at work, we find that households with tertiary-educated members register higher agricultural gross income per unit of land. Their contribution to agriculture is also suggested by satellite-based spatial net primary productivity measures. We inform the larger literature on structural transformations and contend that such transformations can also happen within rural areas.
Keywords: I25; J24; O11; O13; 330; rural; transformations; tertiary education